Hubungan Kebahagian Pernikahan dan Dukungan Sosial terrhadap Penerimaan Diri pada Ibu Anak Disabilitas - Hayati, Sri Ayatina; Handayani, Eka Sri; Nurmiati, Nurmiati (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2025)
This study aims to examine the relationship between marital happiness and social support with self-acceptance among mothers of children with disabilities at SLBN 3 Banjarmasin. Marital happiness is influenced by good communication, mutual respect, trust, commitment, and the ability to resolve conflicts and create joyful moments. For mothers of children with disabilities, social support is a key factor in fostering self-acceptance. Those living in supportive environments tend to experience greater well-being than those without such support.This correlational research involved 94 mothers of children with disabilities as respondents. The independent variables were marital happiness (X1) and social support (X2), while the dependent variable was self-acceptance (Y). Data were analyzed using multiple linear regression with the Ordinary Least Squares (OLS) method.The results showed a significant positive relationship between marital happiness and social support with self-acceptance. This indicates that higher levels of marital happiness and perceived social support contribute to greater self-acceptance among mothers raising children with disabilities